Analisa Kerusakan Relay Valve Dan Air Dryer Pada Air Charging System Unit Heavy Equipment Off Highway Truck (OHT) 777D Caterpillar - Mangkona Mangkona; Adriansyah Adriansyah; Baso Cante; Hasan Basri (Politeknik Negeri Samarinda, 2020)
Air is the successor to the Caterpillar 777D Highway Truck Air System. Air is used to supply the braking system on the Caterpillar 777D Highway Truck which is then collaborated with a hydraulic system for the technical braking process. For this reason, the authors analyze the components of the 777D Caterpillar Highway Truck Air System and what damage often occurs and how to repair it. In this case the object examined is the water system component of the Caterpillar 777D Highway Truck. The method used in this research is field observation, literature study, conducting, inspection with several units that improve the schedule and scheduled repairs. According to the appropriate literature, component damage that occurs in air systems is damage to the system and wear and tear on components. The study was conducted by conducting a visual inspection and measurement, then an analysis of the assessment of the appropriate data literature was carried out. The results found damage to the maintenance component that is not really a component relay valve and air dryer on the air filling system.